Respuestas
Respuesta dada por:
0
Para un Sistema Indeterminado se cumple:
![\frac{a}{3} = \frac{8}{4} = \frac{k+4}{k} \frac{a}{3} = \frac{8}{4} = \frac{k+4}{k}](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%7D%7B3%7D+%3D++%5Cfrac%7B8%7D%7B4%7D+%3D+%5Cfrac%7Bk%2B4%7D%7Bk%7D++)
Entonces:
![\frac{a}{3} = \frac{8}{4} \frac{a}{3} = \frac{8}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%7D%7B3%7D+%3D++%5Cfrac%7B8%7D%7B4%7D+)
4a = 3*8
a = 24/4
a = 6
Y:
![\frac{8}{4} = \frac{k+4}{k} \frac{8}{4} = \frac{k+4}{k}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B4%7D+%3D+%5Cfrac%7Bk%2B4%7D%7Bk%7D)
8k = 4*(k+4)
8k = 4k + 16
8k - 4k = 16
4k = 16
k =16/4
k = 4
Por lo tanto, a*k
a*k = 6 * 4 = 24
Saludos.
Entonces:
4a = 3*8
a = 24/4
a = 6
Y:
8k = 4*(k+4)
8k = 4k + 16
8k - 4k = 16
4k = 16
k =16/4
k = 4
Por lo tanto, a*k
a*k = 6 * 4 = 24
Saludos.
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años